Late Byzantine views of Rus: a reassessment - White, M. (John Benjamins Publishing, 2017)
The late Byzantine empire maintained close ties with the principalities of Rus, but these have been studied almost exclusively in the context of the crises surrounding the appointments of rival metropolitans for the East Slavonic lands in the mid- to late fourteenth century. Other types of sources show, however, that Rus was a subject of serious scholarly interest for several generations of late Byzantine intellectuals. The contemporary politics and geography of Rus, as well as its earlier conversion to Christianity under Byzantine auspices, are discussed in works of various genres and periods. Although the accuracy of these writings is limited, they reveal that the hostility which arose from the machinations in the church hierarchy was not the full story of Byzantine-Rus relations. Indeed, in the empire’s weakened state post-1261, many members of the Byzantine elite viewed Rus as a powerful and reliable (if unsophisticated) supporter whose geopolitical success was thanks largely to Byzantium’s civilising influence.